1999
DOI: 10.1111/j.1600-079x.1999.tb00606.x
|View full text |Cite
|
Sign up to set email alerts
|

Pineal indoleamines and vitamin E reduce nitric oxide‐induced lipid peroxidation in rat retinal homogenates

Abstract: Oxidative damage to retinal cell membranes can lead to sight-threatening ocular diseases. Pineal indoleamines are naturally located and synthesized in the retina, and they possibly protect the retina from oxidative cell damage. In this study, we compared the efficacy of three different pineal indoleamines (melatonin, N-acetylserotonin, and pinoline) with vitamin E, a well-known antioxidant, against nitric oxide (NO)-induced lipid peroxidation (LPO) in rat retinal homogenates. The possible synergistic effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 47 publications
6
84
0
Order By: Relevance
“…Indeed, previous studies have shown a possible role for retinal melatonin as a free radical scavenger within photoreceptors. In isolated photoreceptors from frog retina, melatonin was approximately100 times more potent than vitamin E in inhibiting light-induced oxidative processes (32) and melatonin can reduce the lipid peroxidation induced by nitric oxide in rat retinal homogenates (33). However, supraphysiological concentrations of melatonin may be needed for the antioxidant actions, and MT1 receptor activation appears to play a dominant role in maintaining cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies have shown a possible role for retinal melatonin as a free radical scavenger within photoreceptors. In isolated photoreceptors from frog retina, melatonin was approximately100 times more potent than vitamin E in inhibiting light-induced oxidative processes (32) and melatonin can reduce the lipid peroxidation induced by nitric oxide in rat retinal homogenates (33). However, supraphysiological concentrations of melatonin may be needed for the antioxidant actions, and MT1 receptor activation appears to play a dominant role in maintaining cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of any agent that destroys macromolecules by processes involving free radicals should be decreased if antioxidants, including melatonin, are also present. This has been shown to be the case with melatonin; it has been effectively utilized in vitro and in vivo to combat an incredibly wide number of toxicants including peroxynitrite [22][23][24]65], indomethacin [3], alloxan [26], cisplatin [51], glutamate [29], carbon tetrachloride [62], adriamycin [60], hydrogen peroxide [96], amyloid ß protein [72,73], carrageenan [22][23][24], cerulein [83], nitrilotriacetate [82] and many others [35,87,93,99]. Melatonin has proven equally effective in reducing oxidative damage in conditions where free radical involvement has been established; such situations include ischemia/reperfusion injury [22,111], biliary obstruction [59], ionizing radiation [110], etc.…”
Section: Discussionmentioning
confidence: 99%
“…One molecule with interesting neuroprotective actions and ocular hypotensive effects is melatonin (N-acetyl-5-methoxytryptamine) (Rowland et al, 1981;Siu et al, 1999;Siu et al, 2006;Alarma-Estrany et al, 2007). This molecule and some of its derivatives produce a marked reduction in IOP when topically applied (Pintor et al, 2001(Pintor et al, , 2003Serle et al, 2004;Ismail and Mowafi, 2009;Alarma-Estrany et al, 2008, 2011.…”
Section: Introductionmentioning
confidence: 99%